إنفاق المال في سبيل الله بين المضمون العقدي والدور الاستخلافي للإنسان - باي أحمد عامر (جامعة الوادي University of Eloued, 2024)
Spending the money for the sack of Allah Almighty is one of the opportunities to get great reward which had been emphasised in multipled Quranic verses between obligation and recomondatin, it was one of the sides of Islamic legislation based on creed principles and aimed to achieve set of religious objectives in the economic framework of the individual and society, moreover, it produces their outcomes in the light of overall role of human being. The article in this regard seeks to shed light on the creed components concerning the behaviour of Muslim in spending money, in sense of provision of sustenance for servants is a divine act, the subject of spending is created and owned by Allah, the divine legislation will required human commitments to Allah's commands, then the article mentioned the most important results of previous behaviour intended for achieving human stewardship in two presented sections: advancement of the soul and purification of it in the path of worshipping Allah. On the other hand, the verture of achieving the purpose of justice and preserving human dignity as well as obtaining divine favor in this worldly life and herafter.
Spending the money for the sack of Allah between creed content and stewrdship role of human being
Keywords: الإنفاق; المال; المضمون العقدي; الدور الاستخلافي; الاقتصاد الإسلامي